Changes in cancer incidence and survival among Aboriginal and Torres Strait Islander children in Australia, 1997–2016. Issue 4 (15th December 2021) - Youlden, Danny R.; Baade, Peter D.; McBride, Craig A.; Pole, Jason D.; Moore, Andrew S.; Valery, Patricia C.; Young, Angela; Aitken, Joanne F.
Abstract: Background: This study reports cancer incidence and survival among Aboriginal and Torres Strait Islander children and other Australian children, and assesses changes over time. Procedure: Data were from the population‐based Australian Childhood Cancer Registry. The study comprised children aged under 15 diagnosed between 1997 and 2016 and with mortality follow‐up until 31 December 2017. Incidence trends were analysed using JoinPoint regression. Five‐year cancer‐specific survival was calculated using the semi‐complete approach with survival comparisons made using multivariable flexible parametric models. Results: Aboriginal and Torres Strait Islander children accounted for 506 of 13, 299 eligible cases (3.8%). Incidence rates for Aboriginal and Torres Strait Islander children across the study period increased by 2.3% annually (95% confidence interval [CI]: +0.6% to +4.0%) and for other Australian children increased by 0.6% annually (95% CI: +0.3% to +0.9%; p = .05). Nonetheless, cancer incidence was consistently lower for Aboriginal and Torres Strait Islander children, with an incidence rate ratio of 0.73 (95% CI: 0.62–0.85; p  < .01) between 2012 and 2016. Survival for Aboriginal and Torres Strait Islander children with solid tumours was 70.6% (95% CI: 62.5%–77.3%) and for other Australian children was 83.5% (95% CI: 82.3%–84.7%; p < .01), with indications of this difference diminishing in recent years. Conclusions: Improvements in identification, particularly in urban areas, most likely accounts for the greater increase in cancer incidence rates among Aboriginal and Torres Strait Islander children. Examination of data on stage at diagnosis and treatment may provide important insights into survival for children with solid tumours.